Efficacy of Tuberculosis Vaccine Candidate pcDNA3.1-rpfB in Inhibiting the Growth of Mycobacterium tuberculosis In Vitro with Mycobacterial Growth Inhibition Assay - Pujilestari, Ratih; Rukmana, Andriansjah; Karuniawati, Anis (UI Scholars Hub, 2022)
Tuberculosis (TB) is caused by Mycobacterium tuberculosis (Mtb). Bacille Calmette-Guérin (BCG) is the only licensed vaccine against TB, and it is effective in children but not in adults. The Vaccine Research Team, Department of Microbiology FKUI has developed a DNA-based TB vaccine candidate pcDNA3.1-rpfB. This candidate induces immune responses in mice, but its potency is unknown. The gold standard for potency testing of TB vaccine is the challenge method. The BSL3 animal laboratory for the challenge method is currently unavailable at FKUI. Therefore, mycobacterial growth inhibition assay (MGIA) was used as a preliminary test before the in vivo challenge test was conducted. The principle of MGIA is to reculture Mtb in a Mycobacteria Growth Indicator Tube (MGITTM) from co-cultured Mtb with mammalian cells that have been previously treated with pcDNA3.1-rpfB, pcDNA3.1 (negative control), and BCG (positive control). MGITTM shows the time to positivity, which is the time that has lapsed until a positive growth of Mtb is detected. In addition, measurements of interferon (IFN)γ levels by enzyme-linked immunosorbent assay were carried out. This study concluded that pcDNA3.1-rpfB can inhibit the growth of Mtb in vitro and showed no statistical difference from BCG. The IFNγ levels from co-culturing did not correlate with the level of inhibition of the growth of Mtb in vitro.